Schwannoma of Parapharyngeal Space: a Case Report - Katre, M. I. (Indian J Surg, 2013)
The incidence of schwannoma in the head and neck region is between 25 and 45 %. The vestibular nerve is involved in most cases followed by the parapharyngeal space. Schwannoma, also known as neurilemmoma, is a benign neoplasm that originates from the Schwann cells. These cells form the myelin sheath around myelinated peripheral axons. Here, we report a case of parapharyngeal space schwannoma in a 27-year-old female.